Numerical Assessment on the Dynamic Behaviour of Submarine Hoses Attached to CALM Buoy Configured as Lazy-S under Water Waves - Chiemela Victor Amaechi; Facheng Wang; Jianqiao Ye (Journal of Marine Science and Engineering, 2021)
Recent design challenges in ocean observations, energy storage, offloading/discharging, and loading operations in both the offshore-renewable industry have led to advances in the application of catenary anchor leg moorings (CALM) buoys. Due to different seabed profiles, soil stiffness and environmental conditions, there is the need for numerical assessment to investigate the behaviour of the submarine hoses, based on the structural and hydrodynamic behaviour. In this study, experimental and numerical investigations are carried out on the dynamic behaviour of the submarine hoses attached to a CALM buoy in Lazy-S configuration. Six mooring lines are attached to the CALM buoy with a water depth of 100 m in the numerical model. A hydrodynamic model utilising ANSYS AQWA was developed then coupled unto the dynamic model in Orcina’s Orcaflex. The studies were carried out to study the effect of flow angles, wave height, soil stiffness and hydrodynamic loads on the structural behaviour of the submarine hoses. Waves at different angles to the submarine hose affected the effective tension more where the hose bends due to the floats attached. Parametric studies were carried out on both linear and nonlinear seabed models, and recommendations were made from the investigations on the submarine hose models.